Gestão pública e desenvolvimento empresarial em município petrolífero: a experiência de Rio das Ostras - Leite, Bianka Coutinho Alvim Santos (2010)
This work critically analyzes the creation of a configured project as “space” business-oriented managed by the public power of the state of Rio de Janeiro petroliferous city of Rio das Ostras, located in the region of the “Baixadas Litorâneas”, called Special Zone Business (ZEN). The project appears as product of an institutional arrangement stimulated by the interactivity of mechanisms in the scope of the management of public politics, which are: the politics of administrative decentralization and the law of view of royalties of the oil. The idea of that the cities had started to have one definitive autonomy to manage its destinations, imposes a perspective of that it has a necessity of apprehension of new forms of dialogue between the public and the private one, the State and the society aiming at one better quality of life in these localities. One estimates that there is a necessity of institutional arrangements that make possible the action integration and governabilidade of the politics of the cities directed to its business-oriented townspeople and that the related zone, as was idealized, congregates characteristics that canalize this possibility. To explore this assumption a qualitative study was become fulfilled using inquiry resources as research bibliographical, documentary and empirical through which if it searched to understand them pillars of the conception of the ZEN, who is the citizens and the dynamic of business-oriented participation of this new space and how ZEN generates chances for social development to the city and its townspeople for a durable future of the municipality. The results of the research disclose, of a side, determined resultant advances of the joint of the mechanisms of management of public politics that had made possible the ZEN and of another one, the conflituosas dynamic existence that influences the shared use of the ZEN and the reach of its objectives. It is concluded that the strong influence of companies of the segment of the oil in the ZEN prints a paradox to the intention of the project, being able to compromise the future local economic productive diversification, the social development of the municipality and to make it difficult the transformation of Rio das Ostras in enterprising city with sustainability.